Network mapping of climate change priorities in usa: golden cut bipolar q-rofss - Dinçer, Hasan; Yüksel, Serhat; Mikhaylov, Alexey; Pinter, Gabor; Grigorescu, Adriana (My University, 2024)
The purpose of this study is to identify affordable and clean energy-based climate change priorities in USA for the sustainable development. Five factors that can influence clean energy-based sustainable development are weighted with Multi step wise weight assessment ratio analysis approach. Furthermore, selected priorities for the climate change goal of sustainable development are evaluated. The novelty of this study is presenting affordable and clean energy-based climate change priorities for the sustainable development by considering an original fuzzy decision-making model based on M-SWARA and ELECTRE with bipolar q-rung orthopair fuzzy sets and golden cut. Because they include both membership, non-membership and hesitancy, it can be possible to perform more effective analysis. This issue helps to reach more reliable results. The main findings solve the problem that government support has the greatest weight with respect to the clean energy-based sustainable development.
Keywords: Climate Change; ELECTRE; M-SWARA